KINERJA ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BENGKULU TENGAH DALAM MENJALANKAN FUNGSI PENGAWASAN PERATURAN DAERAH - Hardi Hardi; Harius Eko Saputra; Asnawati Asnawati (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
The purpose of this study is to determine the performance of members of the Regional House of Representatives of Central Bengkulu Regency in carrying out the supervisory function of the Regional Regulations. This research was used descriptive method with qualitative approach. The data collectionwere used interview techniques, observation, and documentation. The result of the research shows that the performance of members of DPRD of Central Bengkulu Regency in carrying out the supervisory function of the regional Regulation through the established mechanism that is through work meeting, go down to the field area for checking the monitoring objects , and synchronize the planning documents and the implementation documents. Supervision conducted by members of DPRD of Central Bengkulu Regency implemented after the exit policy. The form of supervision of the Regional Regulation conducted by members of DPRD of Central Bengkulu Regency is directly monitoring the spaciousness, listening to community input, and hearing together to carry out the supervisory function of the existing Regional Regulation. Obstacles faced by DPRD members in carrying out supervisory functions are topography of Central Bengkulu that is difficult to reach, technical constraints, lack of transparency, and openness of Local Government.